Is There Job Polarization in Developing Economies? A Review and Outlook - Antonio Martins-Neto; Nanditha Mathew; Pierre Mohnen; Tania Treibich (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the evidence of job polarization in developing countries. We carry out an extensive review of the existing empirical literature and examine the primary data sources and measures of routine intensity. The synthesis of results suggests that job polarization in emerging economies is only incipient compared to other advanced economies. We then examine the possible moderating aspects preventing job polarization, discussing the main theoretical channels and the existing empirical literature. Overall, the literature relates the lack of polarization as a natural consequence of limited technology adoption and the offshoring of routine, middle-earning jobs to some host developing economies. In turn, the limited technology adoption results from suboptimal capabilities in those economies, including the insufficient supply of educated workers. Finally, we present the main gaps in the literature in developing economies and point to the need for more micro-level studies focusing on the impacts of technology adoption on workers' careers and studies exploring the adoption and use of technologies at the firm level.
Keywords: J24; J63; O33; E24; 330; job polarization; routine intensity; skills; developing countries